Caracterização fisiológica de genótipos de batata (Solanum tuberosum L.) e sua eficiência de uso e resposta quanto ao fósforo - Uliana, Suzi Cerezer (2013)
Phosphorus (P) is one of the macronutrient that most limits crop production, especially of that potato, a crop that is highly responsive to soil fertility. The deficiency of this nutrient occurs in more than half of the world's arable land. This work aimed to study the effect of two contrasting levels of P in potato genotypes through physiological (growth, chlorophyll a fluorescence, photosynthetic pigments) and biochemical parameters (acid phosphatase activity, phosphorus content in tissues), as well as determinate the efficiency and response index to P. The experiment was conducted hydroponically in a greenhouse, using sand as substrate. The treatments consisted of four potato genotypes SMIC148-A (C), SMIF212-2 (M), SMIG145-1 (O) and SMIJ319-7 (S) and two levels of phosphorus (P), 5% P and 50% (2,32 e 23,23 mg L-1) P of the standard solution. Evaluations were performed at 18, 39 and 62 days after transplanting (DAT). The low level of P was responsible for reductions in tuber yield and production of shoot and root, as decreases in the number of leaves and fresh and dry weight of these parts of the plant were found. The activity of the acid phosphatase enzyme was higher on 5% of P in root and lower in the fourth leaf at initial period of cultivation. The concentration of soluble phosphorus (Pi) and total P content in the tissue, were generally lower at the lower phosphorus level that at the highest level. The concentration of the photosynthetic pigments has been generally kept similar between levels. The Fv/Fm and Fv/Fo ratios as well as a transport rate of electrons (ETR1500) for some genotypes had reductions on 5% P. On the basis of P use and response efficiency indexes, genotypes SMIC148-A (C) and SMIF212-2 (M) were classified into NENR and genotypes SMIJ319-7(S) and SMIG145-1 (O) ER. Keywords: Solanum tuberosum, P use efficiency, P response efficiency, acid phosphatase, phosphorus content, a chlorophyll fluorescence, photosynthetic pigments.